2019
DOI: 10.4236/ojog.2019.96088
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Wound Infection Following Caesarean Section: A Case Control Study from Sir Salimullah Medical College & Mitford Hospital in Dhaka, Bangladesh

Abstract: Background: Post caesarean section (CS) wound infection or surgical site infection is a leading cause of prolonged hospital stay or readmission. An understanding of its risk factors is important. Methods: A case control study was conducted in the Department of Obstetrics and Gynecology of Sir Salimullah Medical College & Mitford Hospital, in Dhaka, Bangladesh from January to June 2014 to evaluate the risk factors of postoperative surgical site infection following CS. One hundred patients were studied. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Results shows in table (4) that weak relationships are a proved with Socio-Demographical Characteristics variables, since no significant relationships were accounted at P>0.05. This result is consistent with (4)(18) (17) whose found that Age, parity and previous CS were not significantly associated with wound infection.…”
Section: Responding and Their Socio-demographic Datasupporting
confidence: 92%
“…Results shows in table (4) that weak relationships are a proved with Socio-Demographical Characteristics variables, since no significant relationships were accounted at P>0.05. This result is consistent with (4)(18) (17) whose found that Age, parity and previous CS were not significantly associated with wound infection.…”
Section: Responding and Their Socio-demographic Datasupporting
confidence: 92%
“…The current study has found that being anaemic (Hct < 33%) was a risk factor for SSI post-CS, consistent with other studies [45][46][47]. The prevalence of anaemia in Rwanda was as high as 52.4% in general and 26.4% among pregnant women [48,49].…”
Section: Discussionsupporting
confidence: 91%
“…is survey shows that the most commonly used antibacterial drugs are cephalosporins, which account for 40.31% of all research subjects using antibacterial drugs; followed by penicillin antibacterial drugs, accounting for 16.95% of all antibacterial drugs; aminoglycosides, accounting for 12.54%; quinolones, accounting for 11.18%; and metronidazole/tinidazolem accounting for 8.4%. Figure 7 shows the distribution of antibacterial drugs in surgical patients [22]. Among all the surgical patients, there were 3265 elective surgery patients and 539 emergency surgery patients.…”
Section: Experimental Method It Collects Basic Informationmentioning
confidence: 99%